Synchronizing nuclear import of ribosomal proteins with ribosome assembly - Kressler, Dieter; Bange, Gert; Stjepanović, Goran; Bradatsch, Bettina; Strauß, Daniela; Sinning, Irmgard; Hurt, Ed (Science, 2012)
Ribosomal proteins are synthesized in the cytoplasm, before nuclear import and assembly with ribosomal RNA (rRNA). Little is known about coordination of nucleocytoplasmic transport with ribosome assembly. Here, we identify a transport adaptor, symportin 1 (Syo1), that facilitates synchronized coimport of the two 5S-rRNA binding proteins Rpl5 and Rpl11. In vitro studies revealed that Syo1 concomitantly binds Rpl5-Rpl11 and furthermore recruits the import receptor Kap104. The Syo1-Rpl5-Rpl11 import complex is released from Kap104 by RanGTP and can be directly transferred onto the 5S rRNA. Syo1 can shuttle back to the cytoplasm by interaction with phenylalanine-glycine nucleoporins. X-ray crystallography uncovered how the α-solenoid symportin accommodates the Rpl5 amino terminus, normally bound to 5S rRNA, in an extended groove. Symportin-mediated coimport of Rpl5-Rpl11 could ensure coordinated and stoichiometric incorporation of these proteins into pre-60S ribosomes.